2009
DOI: 10.1007/bf03345676
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between finasteride, flutamide, and finasteride plus flutamide combination in the treatment of hirsutism

Abstract: To investigate the clinical efficacy and safety of the finasteride (5 mg/day) plus flutamide (125 mg/day) combination therapy in unselected women with hirsutism, 44 women were involved in the study. The effects of such combination treatment have not been reported previously. The patients were assigned to 3 treatment groups: 14 patients (group 1) were treated with finasteride (5 mg per day), 16 patients (group 2) were treated with flutamide (125 mg per day), and 14 patients (group 3) were treated with finasteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Many RCTs compared treatment with finasteride (5 mg/day) to other drugs . Finasteride reduced the FG score and hair diameter more than flutamide (250 mg twice/day) after 6 months of therapy, but flutamide was more effective at 12 months .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many RCTs compared treatment with finasteride (5 mg/day) to other drugs . Finasteride reduced the FG score and hair diameter more than flutamide (250 mg twice/day) after 6 months of therapy, but flutamide was more effective at 12 months .…”
Section: Resultsmentioning
confidence: 99%
“…While some studies demonstrated comparable effects between finasteride and flutamide (250–500 mg/day), others showed finasteride to be less effective . The combination therapy of finasteride with flutamide was most efficacious compared to either monotherapy . RCTs showed no significant difference between finasteride and spironolactone (100 mg/day) reductions in hirsutism scores after 6 months, but spironolactone was more effective after 9–12 months .…”
Section: Resultsmentioning
confidence: 99%
“…This is most likely due to the ability of finasteride to block the conversion of testosterone to the much more potent DHT [80]. However, in another study, flutamide was shown more effective than finasteride in treating hirsute women [106]. The efficacy of finasteride as compared to flutamide needs further verification.…”
Section: Androgen/ar In Hirsutismmentioning
confidence: 99%
“…Other trials suggested that spironolactone and flutamide were more effective than finasteride [27,28]. In women with hirsutism, finasteride is used in doses of 2.5-7.5 mg/d.…”
Section: Finasteridementioning
confidence: 99%